PERILAKU DEBITUR DALAM MENENTUKAN PEMBIAYAAN SYARIAH (STUDI KASUS PADA BEBERAPA BPRS DI WILAYAH TANGERANG DAN BEKASI) - Hasnil Hasyim (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2017)
Syariah banking as one of increasing financial institution is hoped to be one ofthe alternative solution to overcome the economic crisis in Indonesia. It is dueto the fact of the bank’s capability to survive during the crisis where most ofthe conventional banks experienced bankruptcy which was caused by the highrate of interest resulting in the liquidity weaken. The positive impact of thesyariah banking existence is the effective of the intermediary function of abank,that is financing allocation at real sektor resulting in 100 % of Loan toDeposite Ratio (LDR) amount. This has a direct influence in developing thecommunity’s economy and in reducing the unemployment number.Theoritically, the high amount of LDR has a positive correlation to credit riska research on the debtor behavior and faktor influencing them in determiningthe syariah financing is conducted so that the default risk can be minimize.Key word: debitor behavior, syariah banking